Immobilization of Pepsin onto Chitosan Silica Nanobeads with Glutaraldehyde as Crosslink Agent - Sari Edi Cahyaningrum; Maria Monica Sianita (Bulletin of Chemical Reaction Engineering & Catalysis, 2014)
Glutaraldehyde crosslinked chitosan - silica nanobeads have been used as a support in the immobiliza-tion process of pepsin. The effect of pH, pepsin concentration, and temperature on the characteristics of both free and immobilized pepsin had been investigated in this study. The results showed that the im-mobilized pepsin has wider pH range, better capacity, performance and stability to high temperatures compared with those of free pepsin. The immobilized pepsin can be used for 8 to 10 times at which the activity remains 20%, whereas the free pepsin can only be used once. These results suggested promis-ing applications of immobilized enzyme as biocatalyst. © 2014 by Authors, Published by BCREC Group. This is an open access article under the CC BY-SA License (https://creativecommons.org/licenses/by-sa/4.0)